Pengaruh Sistem Keuangan Non-Bunga terhadap Perkembangan Ekonomi di Gorontalo (Analisis Kualitatif Deskriptif 2020–2024) - kurniati kurniati; Sri Dewi Yusuf (Program Studi Akuntansi, 2025)
Abstract:The financial sector is one of the sectors that can influence regional economic growth and plays an important role in triggering the economic growth of a region. This study aims to see the influence of the non-interest financial system on economic development in Gorontalo. The analytical method used is Principal Component Regression Analysis. The results obtained that the development of the financial sector of Islamic banks and non-interest financial institutions in Gorontalo on the regional economy in the Gorontalo region consisting of financial sector variables, namely assets, the amount of credit disbursed, Third Party Funds and the number of non-interest institutions with legal entities, each of which can positively and significantly influence the increase in regional economic growth in the Gorontalo region. The number of non-interest institutions with legal entities has the most significant influence on the increase in the regional economy in the Gorontalo region. Therefore, as input, suggestions or recommendations, the regional government, monetary authorities and the Financial Services Authority (OJK) in its implementation need to synergize with ministries, banks, domestic institutions to increase the role of the non-interest financial sector, including those related to the formation of physical capital accumulation and the distribution of non-interest credit that has an impact on regional development in the Gorontalo region. Keyword: Islamic finance, Islamic banking, Islamic bank, finance, financial systems, banks, banking system. Abstrak: Sektor keuangan merupakan salah satu sektor yang dapat mempengaruhi pertumbuhan ekonomi regional dan memegang peranan penting dalam memicu pertumbuhan ekonomi suatu daerah. Penelitian ini bertujuan melihat pengaruh sistem keuangan non bunga terhadap perkembangan ekonomi di Gorontalo. Metode analisis yang digunakan ialah Analisis Regresi Komponen Utama. Diperoleh hasil bahwa perkembangan sektor keuangan dari Bank syariah dan lembaga keuangan non bunga di Gorontalo terhadap perekonomian regional di wilayah Gorontalo yang terdiri dari variabel sektor keuangan yaitu aset, jumlah kredit yang disalurkan, Dana Pihak Ketiga dan jumlah lembaga non bunga berbadan hukum yang masing-masing dapat mempengaruhi peningkatan pertumbuhan ekonomi regional di wilayah Gorontalo secara positif dan signifikan. Jumlah Lembaga Non Bunga yang berbadan hukum memiliki pengaruh yang paling signifikan terhadap peningkatan perekonomian regional di wilayah Gorontalo. Oleh karenanya sebagai masukan saran atau rekomendasi maka Pemerintah daerah, otoritas moneter dan OJK dalam pelaksanaannya perlu bersinergi dengan kementerian, perbankan, lembaga domestik guna meningkatkan peran sektor keuangan Non Bunga diantaranya berkaitan dengan pembentukan akumulasi modal fisik dan pemeratan persebaran kredit Non Bunga yang berdampak terhadap pembangunan kewilayahan di wilayah Gorontalo. Kata kunci : Keuangan Islam, Perbankan Islam, Bank Islam, Keuangan, Sistem Keuangan, Bank, Sistem Perbankan.